Alan H. Sommerstein, Menander: Epitrepontes, Bloomsbury Ancient Comedy Companions, London; New York: Bloomsbury Academic, 2021, 152 pp., £70.00. ISBN 978-1-350-02364-2 - Cartlidge, Ben (Exemplaria Classica, 2021)